INTRINSIC VS. EXTRINSIC MOTIVATION: WHICH DRIVES HIGHER PERFORMANCE IN HIGH-PRESSURE JOBS? - Rian Irvandi; Oktavianti; Rizki Eka Putra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study investigates the impact of intrinsic versus extrinsic motivation on performance and well-being in high-pressure professions. Against a backdrop of high burnout rates in fields like medicine and finance, the literature reveals a complex interplay: intrinsic motivation is linked to resilience and creativity, while extrinsic rewards can undermine intrinsic drive via the overjustification effect. Using a mixed-methods approach, this research combined quantitative surveys with qualitative interviews. Results demonstrated a strong positive correlation between intrinsic motivation and both high performance ratings and low burnout. Extrinsic motivation showed a more complex, curvilinear relationship. The discussion proposes a "Motivational Hierarchy" where intrinsic factors form the essential foundation, and extrinsic rewards are most effective as supporting enablers. The conclusion urges organizations to cultivate autonomy, mastery, and purpose to foster sustainable high performance.